Iḥsānī social capital: an exploration into faith-inspired unique model - Malik, Maszlee (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2014)
Post-developmentalist discourse suggests, amongst others, the effective role of social capital to development in its own unique way. Additionally, culture, religion, social networks and family institutions as part of the motivations that lead to “social capital” are proposed by some researchers to have their significant role in the re-constructed concept of development, which transcend beyond growth and materialistic barometer. This study is an attempt to explore how IslÉm could contribute towards development of societies by establishing a unique model of social capital from its explicit ontological worldview through a directed descriptive epistemology. A deductive method is applied to its epistemological sources in explaining the emerging conceptual approach of “iḥsānī social capital” that will lead towards development within the framework of „Social Capital‟.